North woods ebook A novel. - Mason, Daniel (2023)
NATIONAL BESTSELLER • A NEW YORK TIMES BOOK REVIEW TOP TEN BOOK OF THE YEAR A WASHINGTON POST TOP TEN BOOK OF THE YEAR • FINALIST FOR THE NATIONAL BOOK CRITICS CIRCLE AWARD AND THE MARK TWAIN AMERICAN VOICE IN LITERATURE AWARD A sweeping novel about a single house in the woods of New England, told through the lives of those who inhabit it across the centuries—“a time-spanning, genre-blurring work of storytelling magic” ( The Washington Post ) from the Pulitzer Prize finalist and author of The Piano Tuner and The Winter Soldier . “With the expansiveness and immersive feeling of two-time Booker Prize nominee David Mitchell’s fiction ( Cloud Atlas ), the wicked creepiness of Edgar Allan Poe, and Mason’s bone-deep knowledge of and appreciation for the natural world that’s on par with that of Thoreau, North Woods fires on all cylinders.”— San Francisco Chronicle New York Times Book Review Editors’ Choice • A BEST BOOK OF THE YEAR: Time, The Boston Globe, NPR, Chicago Public Library, The Star Tribune, The Economist, The Christian Science Monitor, Real Simple, Kirkus Reviews, Publishers Weekly, Library Journal, Bookreporter When two young lovers abscond from a Puritan colony, little do they know that their humble cabin in the woods will become the home of an extraordinary succession of human and nonhuman characters alike. An English soldier, destined for glory, abandons the battlefields of the New World to devote himself to growing apples. A pair of spinster twins navigate war and famine, envy and desire. A crime reporter unearths an ancient mass grave—only to discover that the earth refuse to give up their secrets. A lovelorn painter, a sinister con man, a stalking panther, a lusty beetle: As the inhabitants confront the wonder and mystery around them, they begin to realize that the dark, raucous, beautiful past is very much alive. This magisterial and highly inventive novel from Pulitzer Prize finalist Daniel Mason brims with love and madness, humor and hope. Following the cycles of history, nature, and even language, North Woods shows the myriad, magical ways in which we’re connected to our environment, to history, and to one another. It is not just an unforgettable novel about secrets and destinies, but a way of looking at the world that asks the timeless question: How do we live on, even after we’re gone?